Retinol Binding Protein-4 Is Associated with TNF-α and Not Insulin Resistance in Subjects with Type 2 Diabetes Mellitus and Coronary Heart Disease - Al-Daghri, Nasser M. (IOS Press, 2009)
We studied the association between RBP4 and various markers related to insulin resistance and diabetic complications as well as inflammatory markers in Saudi population suffering from type 2 diabetes and coronary heart disease. Patients with type 2 diabetes were divided into 3 groups according to the type of treatment and involvement of coronary artery disease. Serum RBP4, TNF-α, insulin, CRP, resistin, leptin and adiponectin were analysed in all samples. RBP4 levels increased significantly in the group of diabetic subjects treated with oral hypoglycemic agents and diabetic patients with coronary heart disease (30.2 ± 11.8; 33.4 ± 13.6 respectively), while there was no significant change in the other group for diabetic subjects on low-carbohydrate diet (25.1 ± 10.9) compared to control group (22.6 ± 9.5). RPB4 levels were positively correlated with TNF-α in the group of diabetic subjects on oral hypoglycemic agents and diabetic patients with coronary heart disease (r = 0.52, P < 0.05; r = 0.58, P < 0.05 respectively). No correlations were found between RBP4 levels and insulin resistance in all studied groups. Our findings suggest that serum RBP4 levels is associated with pro-inflammatory cytokine (TNF-α) and is not associated with insulin resistance among patients with type 2 diabetes and coronary heart disease.